(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Depending on the enrichment levels, enriched uranium can be used for many purposes, such as the fabrication of fresh fuels for power and research reactors. Furthermore, under the 1968 Treaty on the Non-Proliferation (NPT), the states, specifically non-nuclear-weapon states of comprehensive safeguards agreements, should be inspected and verified to prove "peaceful use" commitments. Consequently, verifying the enrichment process and the percentage is considered an essential element for investigation purposes. The primary motivation of this paper is to estimate and validate U3O8 samples enrichment percentage using innovative formula. The enrichment calculations were conducted using certified safeguarded nuclear materials with varying low enriched uranium (LEU) ratios, both experimentally with a HpGe detector and computationally with Python 3.10 code. The results prove precise and acceptable values compared to the certified declared enrichment percentage (from depleted 0.32% - 4.5%) with differences in the range of 1⁓ 3.8%. The new formula used in this work applies to national, regional, and international safeguards inspection targets.